ANALISIS PERMINTAAN DAN PENAWARAN MAKANAN KHAS LANGKITANG DI PANTAI PADANG - Waryono -; Youmil Abrian; Hijriyantomi Suyuthie (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Padang Beach has a typical culinary tour like Langkitang. Typical food is one of the factors supporting a region's famous. This study aims to analyze the demand and supply of typical food langkitang in Padang Beach. In particular it aims to analyze the market balance that is influenced by the price of the goods itself, the price of the substitute, the consumer's income, the number of buyers, the cost of production, and the number of producers in the market. The type of research conducted in this study is the type of descriptive quantitative research by survey method. The population of this study are visitors who buy typical food Langkitang and typical food vendors Langkitang which has a stall in the area of ​​Padang Beach. The sampling technique used is purposive sampling, the buyer is 10 people based on the number of samples from the merchant as many as 10 people, with the assumption that 1 trader 1 buyer. Data collection techniques used were observation, interview, documentation, and questionnaire. The data obtained will be analyzed and interpreted in accordance with the objectives and research hypotheses that have been proposed. The analysis was conducted using simultaneous equation model and market balance equation method. Based on the results of this study can be emphasized that the demand and supply of typical food Langkitang in Padang Beach has reached the point of market balance, which is at the equilibrium price of Rp. 4,600, - the proportion with the balance quantity of 32 servings. This means that the equilibrium price will determine the quantity of balance between demand and supply of typical food of Langkitang in Padang Beach. Break event point is on sale of 21 servings of Langkitang with revenue of Rp. 105.000, -.